A Survey on Growing Cult Activities and Food Insecurity in Ekpeye Ethnic Nationality, Rivers State - Ebah, Emmanuel John; Emeodu, Elijah Nwabueze (Research Parks Publishers, 2022)
The persistent occurrence of cult wars and activities with their attendant effects on food security led to this study on growing cult activitiesand food insecurity in Ekpeye ethnic nationality, Rivers State. Three research questions and objectives were used to guide the study. The theoretical framework adopted by this study is the anomic theory propounded by Robert K. Merton. This study used the survey research design to elicit data from respondents, witha population of one hundred and thirty thousand (130,000) people. The sample size was four hundred (400) people generated through the Taro Yamane method. The respondents selected were farmers, traditional rulers, business owners/traders and youth representatives. Four (4) communities were selected for this study viz: Ogbologbolo, Ombor, Odiemudie and Oyigba. The purposive sampling technique, quota sampling and accidental sampling techniques were used. The instrument used was a questionnaire. Data were analyzed using charts, mean and standard deviation. Findings of this study revealed that cult activities have negatively impacted agricultural production and that agricultural activities in the area were almost completely suspended as a result of cult activities. Secondly, the struggle for supremacy among the cult groups affects the development, security of farmers as well as food security.